Therapeutic Effect and Possible Herb Drug Interactions of Ginger (Zingiber officinale Roscoe, Zingiberaceae) Crude Extract with Glibenclamide and Insulin - Al-Omari, Ihsan L.; Afifi, Fatma U.; Salhab, Abdulazim S. (Pharmacognosy Communications)
Background: Zingiber officinale aqueous extracts have traditionally been used by diabetic patients in Jordan. Objective: The present study aims to evaluate the hypoglycemic and antihyperglycemic effects of ginger crude extract (GCE) in normoglycemic- and streptozotocin (STZ)- diabetic- rats and to assess the possible herb-drug interactions with glibenclamide and insulin. Materials and Methods: Oral glucose tolerance test (OGTT) was determined for GCE at concentrations 25, 50 and 100 mg/kg body weight (BW). GCE was administered to normoglycemic rats as a single dose (1 day) and as a daily dose for 1 week. STZ diabetic rats were treated with the same GCE concentrations (25, 50 and 100 mg/kg BW) together with glibenclamide (5 mg/kg BW) or insulin (1.2 IU/kg BW). Results: Single administration of GCE showed a significant decrease in blood glucose level (BGL) in normoglycemic rats at 1 and 2 h (50 mg/kg BW; p<0.001) while one week administration of GCE did not improve BGL. In STZ- diabetic rats GCE (25 and 50 mg/kg BW) decreased non-fasting BGL (N-FBGL) significantly (p<0.001) at 1.5, 2.5, 3.5 and 4.5 h. The combinations of Glibenclamide (5 mg/kg BW) and GCE at doses (25 or 50 mg/kg BW) exhibited after 4.5 h a significantly reduction in the N-FBGL 26.3% (p<0.001) and 25.1% (p<0.01) respectively; while glibenclamide alone exhibited 7.9% reduction. Also co-administration of GCE (50 mg/kg BW) with insulin caused a significant reduction in the N-FBGL at 2.5 (p<0.001) and 3.5 h (p<0.01) compared to insulin alone. Conclusions: The observed interaction of ginger with glibenclamide and insulin appears to be promising in reducing blood glucose levels and needs further evaluation.
Keywords: Diabetes; ginger; herb–drug interactions; OGTT; STZ- diabetic rats